Implementation Of Electronic Parking Terminal (TPE) Policy In The Regional Public Services Agency (Blud) Parking Department Of Transportation In Bandung City - Yuyun Mulyati; Ani Surtiani (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2022)
ABSTRACT One of the receipts for regional retribution is the revenue from regional levies. Parking levies on public roads are one of the regional levies that contribute to local revenue. The Bandung City Government has implemented the Electronic Parking Terminal (TPE) program as an effort to minimize parking problems in the city of Bandung and to increase parking retribution income. The implementation of TPE still has many problems. TPE does not run optimally, people still choose to pay the parking attendant. The research uses a descriptive qualitative approach regarding the implementation of the Electronic Parking Terminal Program (TPE) Policy in the Regional Public Service Agency (BLUD) Parking at the Bandung City Transportation Service. Data collection techniques used are interview, documentation, and observation techniques. The data analysis uses the data reduction method, and data presentation, while the data validation test uses triangulation. The results of the study indicate that the implementation of the TPE Policy in Bandung City has been implemented but is not optimal, this is indicated by the fact that there are still many users who prefer to pay for parking to the parking attendant. And the ineffectiveness of socialization from the implementers of this program policy so that many people are not aware of the Electronic Parking Terminal program. Several efforts have been made to overcome the obstacles that occur, including by providing education and outreach to all related elements, recruiting employees, increasing the competence of existing Human Resources, conducting periodic coaching and giving rewards, and making proposals for regional regulations to the Legislative.